Serum antibodies in human pancreatic disease. Issue 5 (May 1975) - Lendrum, R; Walker, G
Abstract : An immunofluorescent study of sera from patients with various pancreatic diseases and from controls was carried out using human pancreas as substrate. A reproducible pattern of immunofluorscence, consisting of a coarse granular appearance in the cytoplasm of acinar cells of the pancreas and independent of the ABO blood group system was found. This occurred in 21 of 61 patients with acute pancreatitis; it was not found in other pancreatic diseases, and occurred in only four of 170 control subjects consisting of mixed hospital patients and healthy adults. Preliminary absorption experiments suggest that the antigen is located in the microsomal fraction of pancreatic homogenates and may be organ-specific. The relationship of positive antibody tests to aetiological factors is discussed.